Sustainability vs. dignity in death: Tackling grand challenges through consumer responsibilization and responsible innovation - Bhupesh, M.; Narayan, A.; Rakshit, K.; Sreekumar, V. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
‘Grand challenges’ (GC) in the societal space have garnered much attention. Extant research has highlighted the failure of several top-down innovations in addressing GCs, mainly due to lack of contextual understanding. In this paper, we focus on Indian Hindu funerary practices and how grassrootsresponsible innovation is bringing about change. Our enquiries reveal that, although formal, environmentally sustainable crematoria are available, often members of the marginalized communities do not avail themselves of them, due to the presence of ‘complementary institutional voids’. These voids arise at the interface of formal and informal institutions, due to the complex interplay of inter-community and intra-community dynamics, which have not been explored in the literature. Our findings revealed that, through its grassroots-responsible innovation and consumer responsibilization practices, one social enterprise aiming to promote environmentally sustainable cremation practices succeeded in developing a wood-based cremation system for the marginalized in the community, and afforded them a regained sense of identity.
Keywords: Consumer responsibilization, funerary practices, institutional voids, poverty, responsible innovation, sustainability, India